Effect of Ce-Doping on the Structural, Morphological, and Electrochemical Features of Co3o4 Nanoparticles Synthesized by Solution Combustion Method for Battery-Type Supercapacitors - Radhalayam, D (Elsevier Ltd, 2024)
This study investigates the potential of cerium (Ce) doping to improve the performance of cobalt oxide (Co₃O₄) nanoparticles as battery-type supercapacitor electrodes. Pure Co₃O₄ nanoparticles were synthesized via a solution combustion method and then doped with 2.5 % (Ce-Co3O4) and 5 % Ce (CeO2-Co3O4). Comprehensive characterization, including X-ray diffraction (XRD), Raman spectroscopy, and field emission scanning electron microscopy (FESEM), was used to analyze the impact of Ce doping on the material properties. XRD analysis confirmed the successful incorporation of Ce into the Co₃O₄ structure, with distinct CeO2 phases forming at higher doping levels. Ce doping resulted in decreased crystallite size and peak intensity, indicating reduced crystallinity and increased defect concentration. Raman spectroscopy corroborated these findings, showing a redshift that suggests weakened metal-oxygen bonds and smaller grain sizes due to Ce³⁺ incorporation. FESEM images demonstrated that Ce doping effectively reduced nanoparticle agglomeration, with 2.5 % doping leading to smaller particles and 5 % doping promoting a 2D flake-like morphology with increased porosity. Nitrogen adsorption-desorption measurements revealed a significant increase in surface area and pore volume for CeO2-Co₃O₄, facilitating improved electrolyte diffusion and reduced resistance, thereby enhancing electrochemical performance. Evaluation of the electrochemical properties of undoped and Ce-doped Co₃O₄ materials revealed a battery-like response in a three-electrode configuration. Notably, the CeO2-Co3O4 exhibited a superior specific capacity of 603.3 C g−1 at a current density of 1 A g−1, significantly exceeding the values of 368.5 C g−1 and 127.1 C g−1 achieved by Ce-Co3O4 and undoped Co3O4, respectively. Furthermore, the CeO2-doped Co3O4 demonstrated exceptional cyclic stability, retaining 87 % of its initial capacity after undergoing 5000 charge-discharge cycles at a high current density of 10 A g−1. These results suggest that Ce doping is a promising strategy for optimizing Co₃O₄-based battery-type electrode materials, potentially leading to the development of high-performance and cost-effective energy storage systems. © 2024 Elsevier Ltd and Techna Group S.r.l.